A retrospective clinicopathologic study of lichen planus and lichenoid lesions in the oral cavity - Primasari, Ameta (Padjadjaran Journal of Dentistry, 2009)
Lichen planus is a common oral disorder which may represent the manifestation of varies clinical presentation and microscopic findings. In this retrospective study of 86, cases of oral lichen planus (OLP) were compared with 73 cases of oral lichenoid lesions (OLL). Various clinicohistopathological features were studied. The object of this study was to compare clinical and microscopic findings in order to present evidence that supports the position of true lichen planus. Biopsy specimens were obtained from every patient. The biopsy specimens were fixed in 10 percent formalin, embedded in paraffin, sectioned at 4 microns and stained by means of routine hemotoxylin and eosin procedures. The histologic specimens were examined and evaluated without knowledge of clinical findings. The mean age at presentation of patients with OLP was 42.5 years as compared to 47.0 years for OLL. There was no significant difference between the ethnic groups, site of lesions and the distribution of the clinical presentation. Compare to histopathologic findings, there were only 55% clinical and histological agreement in this study, this because of using strict criteria for oral lichen planus there could be an over diagnosis lesions. This study showed that there were no reliable clinical and histopathological features which could differentiate OLL from OLP. The features in the OLL group were non specific. The patient’s medical history, oral habits or psychological status appeared to be able to alter the classical clinicopathological findings.